PENGARUH PERMAINAN TRADISIONAL KUDA BISIK TERHADAP PENINGKATAN KELINCAHAN SISWA KELAS V SEKOLAH DASAR NEGRI 006 SUKA MAKMUR KECAMATAN GUNUNG SAHILAN KEBUPATEN KAMPAR - Supri Supri; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The whispered horse game which is a group game is a type of game that is very popular with children, so that the whispered horse game can indirectly increase children's interest in moving. The whispered horse game does not require special equipment like sports in general, so this game is very easy to play anywhere. The purpose of this study was to determine the benefits of the whispered horse traditional game on the improvement of the agility of the fifth grade students of State Elementary School 006 SUKA MAKMUR, GUNUNG SAHILAN KABUPATEN KAMPAR. The population in this study were 16 students of SDN 006 SUKA MAKMUR. Given the relatively small number of samples, in this study the entire population was sampled. Thus, the determination of the sample using a total sampling technique (saturated sample). The instrument used in this study was the shuttle run test 5 x 8 which is useful for measuring a person's agility in changing directions. The data obtained were analyzed using the t-test. Based on data analysis and discussion, it can be concluded that there is an effect of the whispered horse traditional game on increasing the agility of grade V students of Elementary School 006 SUKA MAKMUR as proven by the results of tcount 3.887> t table 1.753 at α = 0.05. This proves that by playing the traditional horse game whispering, agility can get better results. Key Words: Whispering Horse Traditional Game, Agility